Tourist perceptions of green tourism in a UNESCO world heritage site: Developing the Seruni model in Jatiluwih, Bali - Dianasari, Dewa Ayu Made Lily; Sunarta, I Nyoman; Arida, I Nyoman Sukma; Adikampana, I Made (Edelweiss Applied Science and Technology, 2025)
This study examines tourists’ perceptions of Jatiluwih, a UNESCO World Heritage Site in Bali, as a green tourism destination. As tourism pressure increases, understanding visitor perspectives is essential for designing inclusive and sustainable community-based tourism strategies. The methodology employed a quantitative approach, with data collected from 115 tourists (85 international and 30 domestic) and analyzed through Exploratory Factor Analysis (EFA). The findings indicate that both international and domestic tourists have positive views of Jatiluwih’s green tourism features, particularly its environmental quality, such as clean air, water, and landscape, which strongly influence visitor satisfaction. For international tourists, six main factors were identified: Sustainability of Environmental and Infrastructure, Understanding through Cultural Immersion, Nature-Based Inclusive Travel Experience, Rich Local Cultural and Economic Experience, Ecotourism Engagement, and Involvement of the Local Community. Conversely, domestic tourists emphasize two primary dimensions: the Sustainability of Environmental and Infrastructure and Cultural Ecotourism. These seven components were integrated into a conceptual model named SERUNI. The SERUNI model provides both conceptual and practical implications for advancing green tourism in Jatiluwih, ensuring that future development harmonizes environmental preservation, cultural integrity, and community empowerment while maintaining the destination’s global appeal as a UNESCO World Heritage Site.